KAJIAN PERENCANAAN KEBUTUHAN BRAKE ASSY PESAWAT BOEING 737-400 DI SALAH SATU PERUSAHAAN PENERBANGAN INDONESIA - Zulham Hidayat, (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Scheduled Air Operator ever face the situation where lack of spare part in the maintenance store. This situation will cause disruption of the aircraft operation and will contribute to delay. Delay will make the on time performance of the airline trend tend to decline. So the operator should has good maintenance system resulting of high reliability of aircraft component. PT. XXX has an Indonesian air operator certificate, operate 8 Boeing 737-400. There is a situation where maintenance store lack of spare part requested by line maintenance. Normally, Spare should be available any time when there is requested from line maintenance. This Spare part component is expensive and need specific time for procurement due to import process take a time. It is need good planning for procurement of the aircraft spare part. In this research will use the reliability method for deciding amount of spare part should be available in the store in one year. It will focus on the brake assembly component. In Boeing 737-400 there is 4 brakes installed on the aircraft.